STUDENTS ENGLISH PROFICIENCY AT LEMBAGA TAHFIZ QURAN - Egista Dwi Eriani; Via Novia Sofiana (Jurnal Ilmiah Pendidikan Citra Bakti, 2023)
Students English Profiency At Lembaga Tahfiz Quran. The purpose of this study is to identify the dominant skill among students who memorize the Quran in tahfiz utrujjah. The findings demonstrate that. According to the aforementioned findings, students' use of English in educational settings where the Quran is taught is mostly through watching and listening. Better than being forced is doing what you can because you begin to love and feel pleased first. Additionally, pupils at the tahfiz utrujjah institution were successful in liking the language and being content with it without being coerced and with the support of their own initiative. Tahfiz Quran Utrrujjah Institution is one of them. One of the non-formal educational facilities, Tahfiz Quran, in the city of Serang-Banten, is open to both children and adults. Students are undoubtedly excellent resources for learning the Quran. The Qur'anic scholar who believes that the Qur'an is a noble text while also critically examining the Qur'anic text in order to discover its meaning. English proficiency show a strong positive correlation with overall academic accomplishment.